Isolated Brainstem Involvement in a Patient with Hypertensive Encephalopathy. (28th February 2013) - Osman, Y.; Imam, Y. Z.; Salem, K.; Al-Hail, H.; Uthman, B.; Deleu, D.
Abstract : Hypertensive encephalopathy typically presents with headache, confusion, and bilateral parietooccipital vasogenic edema. Brainstem edema in hypertensive encephalopathy usually occurs in association with typical supratentorial parieto-occipital changes and is usually asymptomatic. We report here a patient with hypertensive encephalopathy, with isolated brain stem involvement on magnetic resonance imaging (MRI). Rapid treatment of hypertension resulted in clinical and radiological improvement. Prompt recognition of the condition and aggressive treatment of hypertension in such patients is crucial to relieve edema and prevent life-threatening progression.